Socio-economic, demographic and health behaviour heterogeneity as determinants of self-medication: evidence from Portuguese micro data - Vale, S.; Camões, F. (International Conference of the ERCIM WG on Computational and Methodological Statistics (ERCIM 2013), 2013)
Self-medication is defined as the choice by individuals of medicines which are available without prescription to treat their self-diagnosed conditions. It is recognized for having benefits and risks. The benefits of self-medication are identified with greater independence of the patient, the improvement of his/her general condition and a reduction in government expenditures with healthcare. There are, however, several non-negligible risks of self-medication such as incorrect diagnosis, incorrect administration and over dosage or over duration of the treatments and delay in the search for indispensable medical advice. This is translated into benefits and costs for society, and is consequently an important piece of public health and public policy debate. Self-medication is frequently associated with health self-assessment and therefore it can be explained by individual practices towards risk, being susceptible of reporting heterogeneity. In this context, we use Portuguese micro data to identify determinants of self-medication. Using data from 2005 National Survey on Health we relate self-medication with socio-economic and demographic status but also with adverse health behaviour. Among our explanatory variables in a discrete dependent variables model, we include income, education, civil status, the incidence of chronic diseases, age, gender, the prevalence of risky health behaviour (smoking, drinking alcohol and being obese) and the habits of medical prevention. Our expected results are an important relevance of income and education, the individual attitude towards risky health behaviour, and significant gender-differences.